Chest physiotherapy in cystic fibrosis: a comparative study of autogenic drainage and the active cycle of breathing techniques with postural drainage. Issue 2 (February 1995) - Miller, S; Hall, D O; Clayton, C B; Nelson, R
Abstract : BACKGROUND–Autogenic drainage has been suggested as an alternative method of chest physiotherapy in patients with cystic fibrosis. In this study autogenic drainage was compared with the active cycle of breathing techniques (ACBT) together with postural drainage. METHODS–Eighteen patients with cystic fibrosis took part in a randomised two-day crossover trial. There were two sessions of one method of physiotherapy on each day, either autogenic drainage or ACBT. The study days were one week apart. On each day the patients were monitored for six hours. Mucus movement was quantified by a radioaerosol technique. Airway clearance was studied qualitatively using xenon-133 scintigraphic studies at the start and end of each day. Expectorated sputum was collected during and for one hour after each session of physiotherapy. Pulmonary functions tests were performed before and after each session. Oxygen saturation (SaO2) and heart rate were measured before, during, and after each session. RESULTS–Autogenic drainage cleared mucus from the lungs faster than ACBT over the whole day. Both methods improved ventilation, as assessed by the xenon-133 ventilation studies. No overall differences were found in the pulmonary function test results, but more patients had an improved forced expiratory flow from 25% to 75% with autogenic drainage, while more showed an improved forced vital capacity with ACBT. No differences were found in sputum weight and heart rate, nor in mean SaO2 over the series, but four patients desaturated during ACBT. CONCLUSIONS–Autogenic drainage was found to be as good as ACBT at clearing mucus in patients with cystic fibrosis and is therefore an effective method of home physiotherapy. Patients with cystic fibrosis should be assessed as to which method suits them best.